Health Belief of Hypertension Patients in Adherance Consume Drug in the Working Areas of Puskesmas Kalikotes A Phenomenology Study - Istianna Nurhidayati; Marwanti Marwanti; Atik Yuliati (Universitas Respati Yogyakarta, 2020)
Hypertension is called the silent killer, a disease that causes cardiovascular organ damage and undetected for years. Recurrence of hypertension experiencee by sufferers with almost the same symptoms. Recurrence will not occur frequently if the patient adheres to the treatment regimen, especially obediently taking medication. A person can adhere to taking medication based on the health trust he/she has. The study aims to gain in-depth understanding of health belief of patients with hypertension in adherence to taking medication. This research used the qualitative design with phenomenologycal approach. The research sample consisted of seven participants using purposive sampling. The criteria of participan were hypertension patients who participate in the chronic disease management program, have controlled blood pressure for the last three months, declared obedient using a modified questionnaire measuring adherence to taking anti-hypertensive drugs, already suffering from ≥ 2 years and goods verbal comunication in indonesian languge. The data of the research ware collected through structured in-depth interviews, observations and focus group discussion (FGD). The data were analyzed by using the Colaizzi (1978). The results obtained eighteen themes, Thare are the definition of hypertension., signs of increased blood pressure, causes of increased blood pressure, how to regulate blood pressure, compliance with taking medication, obedient motivation to take medication, complications, measures to reduce risk, hypertension severity, more stable body, effects side, time, transportation, signs of the body increasing compliance, increased self-efficacy, quality service, expectations of officers, expectations of service. Conclusion The health belief of hypertension sufferers are good as a basis for making decisions or taking medication in this medication adherence.